Exploring Knowledge Management as a Correlate of SME Performance in Nigeria - Okoli, Ifeanyi. E. Nuel; Nuel-Okoli, Chinenye Maureen; Adani, Nnenne Ifechi (New Advances in Business, Management and Economics Vol. 2, 2025)
This study explored the influence of knowledge management on the performance of selected manufacturing Small and Medium Enterprises (SMEs) in Southeast Nigeria. The research was guided by three specific objectives, research questions, and hypotheses, with variables broken down into distinct components. A survey design was employed, targeting academic staff within the selected SMEs. The study population consisted of 800 individuals, and a sample size of 196 was determined using the Krejcie and Morgan (1970) formula. Data were collected through self-administered questionnaires and analyzed using descriptive statistics (frequency tables and percentages) and inferential statistics (Pearson correlation coefficient and regression analysis). The findings indicated a significant positive relationship between knowledge management and SME performance. Specifically, there was a strong link between knowledge management dimensions—knowledge sharing, acquisition, and protection—and firm performance dimensions such as market share, sales growth, and customer satisfaction. The study concluded that SMEs that actively acquire new knowledge are better positioned to satisfy customers, while those that encourage knowledge sharing among employees achieve higher market share compared to those that restrict knowledge access. The study recommended that SMEs implement effective feedback mechanisms to encourage employees to provide input, share ideas, and ask questions, fostering a culture of continuous improvement and innovation.